The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/etc.4902
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption of Triclosan on Biodegradable Polyhydroxybutyrate Microplastics

Abstract: Biodegradable plastics have been increasingly used as a solution to the problem of plastic pollution in recent years. However, there are few studies on the negative effects of biodegradable microplastics. Triclosan, a widely used disinfectant, is a highly toxic substance. In the present study, the adsorption and desorption processes of triclosan on a type of biodegradable plastics, polyhydroxybutyrate (PHB), were investigated and also compared with one conventional plastic type, polyethylene. The adsorption eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…A comparative experimental study between MPs from LDPE and biodegradable plastics (starch-based plastic) mulch revealed that MPs from biodegradable plastic mulch has a stronger negative impact on wheat growth than PE mulch, which might be because biodegradable plastic mulch contains 18.3% polybutylene terephthalate and 44.6% PET, which stops starch induced nitrogen movement 16 . Another study on the adsorption and desorption kinetics of PE and PHB MPs also confirmed that triclosan (a common disinfectant used in plastics) equilibrium adsorption and desorption rate of PE is greater than PHB (3431.85 and 9442.27 μg/g, respectively), and PHB easily releases it compared with PE 150 .…”
Section: Terrestrial Ecosystemmentioning
confidence: 71%
See 2 more Smart Citations
“…A comparative experimental study between MPs from LDPE and biodegradable plastics (starch-based plastic) mulch revealed that MPs from biodegradable plastic mulch has a stronger negative impact on wheat growth than PE mulch, which might be because biodegradable plastic mulch contains 18.3% polybutylene terephthalate and 44.6% PET, which stops starch induced nitrogen movement 16 . Another study on the adsorption and desorption kinetics of PE and PHB MPs also confirmed that triclosan (a common disinfectant used in plastics) equilibrium adsorption and desorption rate of PE is greater than PHB (3431.85 and 9442.27 μg/g, respectively), and PHB easily releases it compared with PE 150 .…”
Section: Terrestrial Ecosystemmentioning
confidence: 71%
“…16 Another study on the adsorption and desorption kinetics of PE and PHB MPs also confirmed that triclosan (a common disinfectant used in plastics) equilibrium adsorption and desorption rates of PE is greater than that of PHB (3431.85 and 9442.27 μg g −1 , respectively), and PHB easily releases it compared with PE. 150…”
Section: Microplastics In Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of them, triclosan (TCS) is known to be a persistent endocrine disruptor that can bioaccumulate in different aquatic organisms [111]. Tong et al [112] have shown that the sorption of TCS in bio-MPs of PHB was far higher than in the MW of PE and that TCS could be easily desorbed from PHB and polyethylene under physiological conditions. Their results highlight the problems of PHB bio-MPs, even if the similarity between their laboratory conditions and reality is questionable.…”
Section: Microcosmus Exasperatesmentioning
confidence: 99%
“…The findings demonstrated that BMPs could act as stronger vectors than conventional ones in the environment. Although microplastics have good adsorption properties for pollutants, their migration ability is not high (Tong et al 2021). By establishing a plastic migration model, the researchers predicted that the migration of microplastics was 4-6 orders of magnitude lower than that of other substances migrating with ocean current (Zarfl and Matthies 2010).…”
Section: Can Bmps Act As Stronger Vectors For Chemical Pollutants and Microorganisms?mentioning
confidence: 99%